2023
DOI: 10.1002/fsn3.3662
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, nutraceutical, and nutritional properties of flaxseed (Linum usitatissimum): An insight into its functionality and disease mitigation

Sana Noreen,
Tabussam Tufail,
Huma Bader Ul Ain
et al.

Abstract: Flaxseed (Linum usitatissimum L.) is derived from the flax plant, an annual herb. The primary relevance of flaxseed is in the human nutrition sector, where it is emerging as a significant functional food component due to its high level of active chemicals, which have been linked to health benefits. Flaxseed may be consumed in numerous forms, including milled, oil, and bakery items. The phytochemicals that are present in flaxseed have greatly drawn interest as bioactive molecules beneficial for health. It is na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Lignans are widely distributed in plants, being found in the roots, stems, leaves, flowers, fruits, seeds, and other parts ( Lu and Liu, 1992 ; Wu et al, 2019 ). Recently, researchers have found that higher concentrations of lignans in flaxseed extracts protect against acute myeloid leukemia (AML) when secoisolariciresinol (SECO) released by gastrointestinal bacteria is hydroxylated and demethylated to produce mammalian lignan enterodiol (END) ( Noreen et al, 2023 ). The structural diversity of lignans has been studied in depth, and many lignans have been found to exhibit fatigue-relieving pharmacological activities.…”
Section: Signaling Pathways Affected By Natural Active Ingredients Ag...mentioning
confidence: 99%
“…Lignans are widely distributed in plants, being found in the roots, stems, leaves, flowers, fruits, seeds, and other parts ( Lu and Liu, 1992 ; Wu et al, 2019 ). Recently, researchers have found that higher concentrations of lignans in flaxseed extracts protect against acute myeloid leukemia (AML) when secoisolariciresinol (SECO) released by gastrointestinal bacteria is hydroxylated and demethylated to produce mammalian lignan enterodiol (END) ( Noreen et al, 2023 ). The structural diversity of lignans has been studied in depth, and many lignans have been found to exhibit fatigue-relieving pharmacological activities.…”
Section: Signaling Pathways Affected By Natural Active Ingredients Ag...mentioning
confidence: 99%
“…Laura E Voorrips [ 17 ] showed that ALA was the only n-3 PUFA that was effective at reducing the risk of breast cancer (BC). Based on global medical and nutritional studies [ 9 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], ALA can regulate blood lipids, reduce blood viscosity, lower blood pressure, support weight loss, suppress allergic reactions, inhibit inflammation, affect diabetes and bone health, and inhibit cancer occurrence and metastasis. Therefore, it is necessary to distinguish ALA from other n-3 PUFAs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that soluble‐fiber‐rich whole grains like oats and barley reduce blood cholesterol better than insoluble‐fiber‐rich grains like wheat or rice. Adding dietary fiber, a variety of plant compounds that resist digestion by human gastrointestinal enzymes, lowers cholesterol (Noreen, Tufail, Ul Ain, et al., 2023 ). The structural or matrix fibers (lignins, cellulose, and some hemicelluloses) are insoluble in water, while the natural gel‐forming fibers (pectins, gums, mucilages, and the rest of the hemicelluloses) are soluble.…”
Section: Introductionmentioning
confidence: 99%